Strategic Risk Shifting and the Idiosyncratic Volatility Puzzle: An Empirical Investigation - Chen, Zhiyao; Strebulaev, Ilya A.; Xing, Yuhang; Zhang, Xiaoyan (Management Science, 2021)
We find strong empirical support for the risk-shifting mechanism to account for the puzzling negative relation between idiosyncratic volatility and future stock returns. First, equity holders take on investments with high idiosyncratic risk when their firms are in distress and receive less monitoring from institutional holders as well as when the aggregate economy is in a bad state. Second, the strategically increased idiosyncratic volatility decreases equity betas, particularly in bad states when the market risk premium is high. The negative covariance between the equity beta and the market risk premium causes low and negative returns and alphas in firms with high idiosyncratic volatility. This paper was accepted by Tomasz Piskorski, finance.